YOUTH, REVOLUTION, AND REPRESSION. (4th November 2015) - Shadmehr, Mehdi; Haschke, Peter
Abstract : We develop a simple model to study the effect of age structure on the interactions between the state and dissidents. Younger populations are more prone to protest. As the population grows younger, states that can discriminately target repression to different groups, but cannot concede discriminately, decrease repression. In contrast, states that can target concession, but not repression, increase repression. We test these results in nonmilitary single‐party regimes and military regimes without political parties. Moreover, we study state response to dissent in East European communist regimes in the late 1980s, showing that state response was more repressive in countries with younger populations. ( JEL D74)